2021
DOI: 10.1590/s1980-220x2019034103704
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to duration of hospitalization and death in premature newborns

Abstract: Objective: To analyze factors related to prolonged hospitalization and death in premature newborns in a border region. Method: Cross-sectional study, with retrospective data collection, which analyzed 951 medical records of premature newborns hospitalized between 2013 and 2017. The independent variables were maternal age, nationality, prenatal appointments, maternal intercurrences, gestational age, weight at birth, Apgar, complications; the dependent variables were days of hospitalization, discharge, death, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
6
0
12
Order By: Relevance
“…Embora sejam RNs a termo, o baixo peso da amostra associou-se com maior tempo de internação, sendo o ganho de peso um pré-requisito para a alta 20 . Já Rohininath et al 21 , em um estudo sobre admissões de bebês pesando mais de 2.500g na UTIN, verificaram que a porcentagem de bebês a termo foi de 54% de todas as admissões na UTIN e, desses, 12,8% não exigiam cuidados de alto nível, sendo consideradas internações potencialmente evitáveis.…”
Section: Discussionunclassified
“…Embora sejam RNs a termo, o baixo peso da amostra associou-se com maior tempo de internação, sendo o ganho de peso um pré-requisito para a alta 20 . Já Rohininath et al 21 , em um estudo sobre admissões de bebês pesando mais de 2.500g na UTIN, verificaram que a porcentagem de bebês a termo foi de 54% de todas as admissões na UTIN e, desses, 12,8% não exigiam cuidados de alto nível, sendo consideradas internações potencialmente evitáveis.…”
Section: Discussionunclassified
“…Despite being full-term newborns, the low weight of the sample was associated with longer hospitalization time, and weight gain was a prerequisite for discharge 20 . Rohininath et al 21 , in a study on admissions of infants weighing more than 2,500g in the NICU, found that the percentage of full-term newborns was 54% of all admissions to the NICU, and out of these, 12.8% did not require high-level care, and were considered potentially avoidable hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…The first 60 minutes of a premature NB's life, referred to as the Golden Hour, are essential for maintaining NB life. The Golden Hour strategy focuses on specific goals, developed in Neonatology (2)(3) .…”
Section: Introductionmentioning
confidence: 99%